Post implementation of goods and services tax (GST) in Malaysia: tax agents’ perceptions on clients’ compliance behaviour and tax agents’ roles in promoting compliance - Muhammad, Izlawanie (EDP Sciences, 2017)
The Malaysian government introduced the Goods and Services Tax (GST) starting from 1 April 2015 to enhance the revenue collections and mitigate the transfer pricing manipulation.Tax agents play a significant role to help businesses to comply with GST law and regulations. After one year of GST implementation, it is vital to understand tax agents’ perceptions on clients’ compliance behaviour and tax agents’ roles in influencing compliance.A total of 30 registered tax agents completed a survey questionnaire. The analysis shows that tax agents devote their time to provide advice to their clients on meeting their GST requirements, and recording and reporting of GST transactions.Tax agents assert that clients pass on their GST responsibilities to tax agents to some extent.Tax agents also perceive that clients’ compliance level is low because clients occasionally submit GST03 after the deadline, compromise the accuracy of GST03 in order to get it done on time and intentionally make errors in their records.In terms of tax agents’ role in promoting compliance, the tax agents strongly agree that it is important for them to act as trusted advisors for their clients.After one year of GST implementation, this is the first study that explores tax agents’ perceptions on clients’ compliance and tax agents’ roles in promoting compliance.The findings benefit the Royal Malaysian Customs Department (RMCD) in assisting tax agents and the public for future compliance.Similar study should be adopted by countries that have recently implemented GST (for example, India) and it should be conducted to other GST players (i.e. taxpayers and RMCD officers) on annual basis to analyse the behavioural trends and identify weaknesses in GST administration.